Afghan Women's Perceptions of Coronary Behavioral Fluctuations in Families: A Case Study of Bamyan Province - Mutamed, Mohammadullah; Sadati, Ahmad Kalata; Mohammadi, Kimya (Journal of Social Sciences - Kabul University, 2021)
This study seeks to understand and analyze the impact of the COVID-19 pandemic on behavioral fluctuations within Afghan families, particularly among women. Given the widespread effects of the pandemic across Afghanistan, this research focuses on Bamyan province, where twelve women who experienced the pandemic firsthand were interviewed. The study employs a snowball sampling method, and data were analyzed through coding techniques. The research findings highlight significant behavioral shifts within families due to pandemic-induced stress and uncertainty.